Tabel Volume Pohon â€œBerkhoutâ€ pada Hutan Alam Tanah Kering di Wilayah Kapuas Hulu, Provinsi Kalimantan Tengah (The Local Table of Volume on the Dry Land Natural Forest at the Upper Stream Kapuas, Central Kalimantan Province) : Wahyudi - JHT, Admin (Jurnal Hutan Tropika, 2016)
ABSTRACT The local table of volume is needed to determine volume of stands just based on their diameters in the certain of region. The research was aimed to create the local table of volume based on three groups of trees, namely Shorea groups, Dipterocarp non Shorea groups, and non Dipterocarp groups. Location of research was in Sub-District of Kapuas Hulu and Mandau Talawang, District of Kapuas, Central Kalimantan Province. Research method using tabel of volume equations in the form of Berkhout model that in order of regression equations. Research result showed that table of volume to Shorea groups, Dipterocarp non Shorea groups, and non Dipterocarp groups on the those two sub-districts are V = 0.00012D2.549, V = 0.000172D2.4319, and V = 0.00009D2.6292 respectively. According to the F test and R2 value, the local tables of volume are suitable used to predict the volume of the stands in the sites and their surrounding. Keywords: Dipterocarp, regression, shorea, table of volume.